Think Before You Take: Understanding Adult Medication Literacy in Saudi Arabia - Alhomoud F; Alsaeed W; Alzainaldain F; Alelq K; Alhomoud FK; Alamer KA; Alsultan MM; Alqarni YS; Alshehail B; Alhifany AA (Patient Preference and Adherence, 2025)
Faten Alhomoud,1 Walaa Alsaeed,1 Fatimah Alzainaldain,1 Kawthar Alelq,1 Farah Kais Alhomoud,1 Khalid A Alamer,1 Mohammed M Alsultan,1 Yousef Saeed Alqarni,1 Bashayer Alshehail,1 Abdullah A Alhifany2 1Department of Pharmacy Practice, College of Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Clinical Pharmacy Department, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Faten Alhomoud, Department of Pharmacy Practice, College of Pharmacy, Imam Abdulrahman Bin Faisal University, Dammam, 31952, Saudi Arabia, Tel +966133335547, Email falhomoud@iau.edu.saBackground: Poor medication literacy may lead to serious health risks. Nevertheless, very little research has examined medication literacy in Saudi Arabia. Thus, this study assessed medication literacy and factors associated with poor medication literacy.Methods: A descriptive, cross-sectional study was conducted, with eligibility criteria including individuals aged ≥ 18 years, speaking Arabic or English, and residing in Saudi Arabia. Eligible participants completed an online, self-administered survey disseminated through social media platforms over a two-month period. Horvat’s Medication Literacy Assessment Questionnaire was employed. The analysis used regression in SPSS version 29 to identify predictors of medication literacy.Results: A total of 815 participants were included. Most were female (75.7%), aged 18– 24 years (50.1%), and held undergraduate degree (47%). The median (IQR) medication literacy score, assessed using Horvat’s Medication Literacy Assessment Questionnaire (score range: 0– 29), was 22.0 (18– 24). Results showed a relatively poor level of medication literacy, with 50% of participants scoring below the average of correct answers. Most problems were found in items related to dosing, requiring understanding information from longer texts and numerical skills. Other issues included refills, drug use in pregnancy, storage and disposal, expiration date, adverse effects, drug interactions, missed doses, label understanding, tablet splitting, and duration of therapy. Multiple linear regression revealed significant predictors. Lower educational levels were associated with reduced scores (β = − 1.765, p = 0.009 for high school or below; β = − 5.872, p = 0.016 for diploma). Smaller households were associated with higher scores (β = 1.252, p = 0.031 for 1– 4 members; β = 1.255, p = 0.021 for 5– 8 members). Prescription medications use (β = 2.375, p < 0.001) and less frequent pharmacists consultation (β = 3.602, p = 0.001) were positively associated with higher scores.Conclusion: Medication literacy among study participants requires improvement, especially in areas involving dosing instructions and numerical understanding. Targeted interventions are necessary for those with inadequate literacy levels.Keywords: literacy, health, health literacy, medicine, drug, therapy, cross-sectional studies, health surveys, Saudi Arabia